Detailed genetic and clinical analysis of a novel de novo variant in HPRT1: Case report of a female patient from Saudi Arabia with Lesch–Nyhan syndrome - AlBakheet, Albandary; AlQudairy, Hanan; Alkhalifah, Joud; Almoaily, Sheikhah; Kaya, Namik; Rahbeeni, Zuhair (Frontiers in Genetics, 2023)
Background: Hypoxanthine-guanine phosphoribosyltransferase (HPRT1) deficiency is an inborn error of purine metabolism responsible for Lesch–Nyhan syndrome (LNS). The disease is inherited in an X-linked recessive manner and predominantly affects male individuals. Female individuals can carry a mutation as heterozygotes, but typically, they are asymptomatic because of the random inactivation of the affected allele. Nevertheless, although rare, heterozygote female individuals may manifest LNS with full characteristics. Herein, we describe a female patient from Saudi Arabia with LNS. Results: The patient (a 4-year-old girl) presented with typical characteristics of the disease, which include global developmental delay, self-mutilation, hyperuricemia, hypotonia, speech delay, spasticity, and seizures. Her general biochemical laboratory results were normal except for high levels of uric acid. The abdominal MRI, mostly unremarkable, showed bilateral echogenic foci within the renal collecting system. Genetic testing (whole-exome sequencing, iterative variant filtering, segregation analysis, and Sanger sequencing) pointed a novel de novo frameshift variant in HPRT1. X-inactivation assay using HpaII showed the presence of a 100% skewed X chromosome carrying the affected allele. RT-PCR of the cDNA indicated complete loss of the expression of the normal allele. Conclusion: Our study presents a female patient who has a severe case of LNSand found to be the 15th female patient with the disease in the world. The study emphasizethe need for a streamlined protocol that will help an early and accurate diagnosis of female LNS patients to avoid unnecessary interventions that lead to costly patient care.